Effect of blade pitch angle on the aerodynamic characteristics of a twisted blade horizontal axis wind turbine based on numerical simulations - Rajendra Roul; Awadhesh Kumar (Institute of Advanced Engineering and Science, 2021)
The present work includes a study of the impact of varying pitch angles and angular velocity on the performance parameters of a horizontal axis wind turbine using computational fluid dynamics. Simulations have been made using commercial Ansys 15 software. Seven pitch angles are chosen for study, i.e., 0° , 5 ° , 10° , 15° , 20° , 25° , and 28°, and two angular velocity values of 1.57 rad/sec and 2.22 rad/sec are used for simulation. The turbulence model used is shear stress transport (SST) K-ω. A detailed study of the influence of pitch angle on the aerodynamic characteristics of the wind turbine is highlighted. Performance parameters like torque and power have been found to exhibit random variability with a change in wind velocity and pitch angle. The verification of computational fluid dynamics (CFD) with the standard empirical formula is highlighted. The best pitch angle is noted for the best power coefficient.